Human Gait Recognition Based on Multiview Gait Sequences. (11th May 2008) - Huang Huang, Xiaxi Xiaxi; Boulgouris Boulgouris, Nikolaos V. Nikolaos V.
Abstract : Most of the existing gait recognition methods rely on a single view, usually the side view, of the walking person. This paper investigates the case in which several views are available for gait recognition. It is shown that each view has unequal discrimination power and, therefore, should have unequal contribution in the recognition process. In order to exploit the availability of multiple views, several methods for the combination of the results that are obtained from the individual views are tested and evaluated. A novel approach for the combination of the results from several views is also proposed based on the relative importance of each view. The proposed approach generates superior results, compared to those obtained by using individual views or by using multiple views that are combined using other combination methods.